The Influence of Interactive Technology and Digital Innovation on Tourists Revisit Interest at the National Museum of Indonesia - Dave Antoro Widjaya; Lamtiar Hema Malini (Darul Yasin Al Sys, 2026)
The post-revitalization transformation of the National Museum of Indonesia has been marked by the adoption of Augmented Reality, Artificial Intelligence, virtual tours, the Immersive Room, digital collections, and various digital platforms; however, the extent to which these technologies influence tourists’ revisit intention requires further empirical examination. This study aims to analyze the influence of interactive technology and digital innovation on tourists’ revisit intention at the National Museum of Indonesia. This study employed a quantitative approach using a survey method. Primary data were collected through a Likert-scale questionnaire administered to 100 respondents who had visited the National Museum of Indonesia during the 2024–2025 period and were interested in revisiting or had already made a return visit in 2026. Respondents were selected using purposive sampling. Data were analyzed using SPSS version 25 through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis. The findings indicate that interactive technology has a positive regression coefficient of 0.142 but does not exert a significant partial effect on revisit intention (t = 1.207; p = 0.231). In contrast, digital innovation has a positive and significant partial effect (β = 0.487; t = 3.298; p = 0.001), indicating that it is a stronger predictor of tourists’ revisit intention. Simultaneously, interactive technology and digital innovation have a significant effect on revisit intention (F = 29.573; p < 0.001), with an R² value of 0.379, explaining 37.9% of the variance in revisit intention. This study concludes that digital innovation is a more dominant factor in encouraging tourists to revisit the National Museum of Indonesia. The findings contribute to cultural tourism and museum management studies by highlighting the strategic role of digital innovation in strengthening tourist experience and post-visit behavioral intention.